Early viral kinetics during hepatitis C virus genotype 6 treatment according to IL28B polymorphisms - Akkarathamrongsin, Srunthron (Baishideng Publishing Group Inc, 2014)
AIM: To investigate the early viral kinetics and interleukin-28B (IL28B) polymorphisms of hepatitis C genotype 6 during pegylated interferon and ribavirin therapy. METHODS: Sixty-five patients with chronic hepatitis C virus (HCV) infection treated with pegylated interferon and ribavirin (PEG-IFN/RBV) were included, of whom 15 (23.1%), 16 (24.6%) and 34 (52.3%) patients were infected with hepatitis C genotype 1 (HCV-1), genotype 3 (HCV-3) and genotype 6 (HCV-6), respectively. Serum HCV-RNA levels were measured frequently during the first 4-wk of therapy. DNA extracted from samples was analyzed for the IL28B single nucleotide polymorphism (SNP) rs12979860 by polymerase chain reaction and direct sequencing. RESULTS: During the first 4-wk of therapy, the mean viral decline for patients with HCV-6 (5.55 ± 1.82 log(10)IU/mL) was comparable to that of patients with HCV-3 (5.55 ± 1.82 log(10)IU/mL vs 5.86 ± 1.02 log(10)IU/mL, P = 0.44) and was significantly higher than patients with HCV-1 (5.55 ± 1.82 log(10)IU/mL vs 4.23 ± 1.99 log(10)IU/mL, P = 0.04). In the HCV-6 group, the first phase (days 0-2) viral decline was significantly higher in patients with the favorable rs12979860 CC than non-CC genotypes (2.46 ± 1.01 log(10)IU/mL/wk vs 1.70 ± 0.67 log(10)IU/mL, respectively, P = 0.045). A statistically insignificant decrease in the second-phase (days 7-28) decline was also found in patients with the CC genotype than those with the non-CC genotype, though not significantly different (1.24 ± 0.64 log(10)IU/mL/wk vs 0.80 ± 0.65 log(10)IU/mL/wk, respectively, P = 0.172). At baseline, the SNP genotype was an independent predictor of rapid virological response but not of sustained virological response. CONCLUSION: The IL28B genotype was linked to an impact on early viral kinetics in response to PEG-IFN/RBV therapy in HCV-6 infected patients.